THE IDENTIFICATION OF MICROPLASTICS IN GILLS AND DIGESTIVE TRACT IN TILAPIA FISH (Oreochromis mossambicus) IN LAKE TOBA - Simbolon, Licia Larosa; Sudibyo, Mufti; Hanim, Nisfa (Universitas Medan Area, 2025)
Microplastics threaten the survival of aquatic organisms including fish in Lake Toba. This study aims to identify the type and abundance of microplastics found in the gills and digestive tract of tilapia (Orochromis mossambicus) in cages and non-cages of Lake Toba, Samosir Regency. Sampling was conducted in February-March 2024 at three stations namely Tanjung Bunga, Palipi, Simarsasar with sampling at each location of 10 caged and non-caged fish each. Extraction of microplastics using the Fenton. Observation parameters included gill weight, gut length, and abundance of microplastics in the gills and digestive tract. The results revealed that the majority of microplastics identified in cages and non-cages were fiber and filament types, with non-cage fish having a higher abundance of microplastics than cage fish.